Alternative regimens for treating prostate cancer using equivalent uniform dose and Monte Carlo methods - Oliveira, Susana (2017)
Introduction - Conventional radiotherapy treatments are administrated with 2 Gy external beam radiotherapy (EBRT) fractions. It has been postulated that prostate cancer would respond to radiotherapy as a slowly proliferating late-responding normal tissue, benefiting from hypo-fractionated regimens. Highly conformed brachytherapy is a treatment option either alone or combined with EBRT. Purpose - To identify alternative radiotherapy regimens for treating prostate cancer using EBRT and low dose-rate brachytherapy (LDRBT) with 125I implants, biologically equivalent to conventional treatments in terms of uniform equivalent dose (EUD). Materials and methods - The EUD concept was used, together with Monte Carlo (MC) methods. Two voxel phantoms were segmented from the computed tomography of patients to obtain the energy deposition derived from the MC simulations of EBRT and LDRBT treatments on a voxel-by-voxel basis. The energy deposition was converted in EUD. Equivalent regimens to EUDs of 72 Gy, 80 Gy, 90 Gy, and 100 Gy were determined for increasing fractions of 1.8–5.0 Gy and amounts of LDRBT from 0 Gy (EBRT exclusive) to 145 Gy. The resulting EUD for rectum was also evaluated. Results - Alternative schemes equivalent, in terms of EUD, were obtained. For example, it is equivalent to an EUD of 72 Gy, 38 × 2 Gy, 20 × 3 Gy or 9 × 5 Gy of EBRT, or 6 × 5 Gy of EBRT plus 50 Gy of LDRBT. The rectum benefits of higher amounts of LDRBT for EBRT fractionations <2.5 Gy and larger fractions for LDRBT dose <50 Gy. Conclusion - Alternative regimens for the treatment of prostate cancer with EBRT and LDRBT are proposed. The rational for the use of brachytherapy becomes less relevant with the increasing therapeutic ratio achieved with hypo-fractionated EBRT.